2019
DOI: 10.1002/dta.2573
|View full text |Cite
|
Sign up to set email alerts
|

1H−15N HMBC NMR as a tool for rapid identification of isomeric azaindoles: The case of 5F‐MDMB‐P7AICA

Abstract: The high frequency of the synthetic cannabinoid receptor agonists (SCRAs) emergence renders this group of new psychoactive compounds particularly demanding in terms of detection, identification, and responding. Without the available reference material, one of the specific problems is differentiation and structure elucidation of constitutional isomers. Herein, we report a simple and efficient flow chart diagram applicable for a rapid nuclear magnetic resonance (NMR) identification and differentiation between az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…To this end, 1 H‐ 15 N heteronuclear multiple bond correlation (HMBC) nuclear magnetic resonance (NMR) spectroscopy has recently been utilized to provide an analytical method for the differentiation of unsubstituted 4‐, 5‐, 6‐, and 7‐azaindole constitutional isomers. Using the latter approach has permitted Martek et al to unambiguously assign the structure of 7‐azaindole 5F‐MDMB‐P7AICA ( 25 ) . The latter work highlights the importance of spectroscopic methods in the continued struggle to monitor a rapidly evolving class of NPS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, 1 H‐ 15 N heteronuclear multiple bond correlation (HMBC) nuclear magnetic resonance (NMR) spectroscopy has recently been utilized to provide an analytical method for the differentiation of unsubstituted 4‐, 5‐, 6‐, and 7‐azaindole constitutional isomers. Using the latter approach has permitted Martek et al to unambiguously assign the structure of 7‐azaindole 5F‐MDMB‐P7AICA ( 25 ) . The latter work highlights the importance of spectroscopic methods in the continued struggle to monitor a rapidly evolving class of NPS.…”
Section: Introductionmentioning
confidence: 99%
“…However, from an impurity profiling perspective, it is noteworthy that the dehalogenation of 1‐bromoadamantane, when in the presence of silver carbonate, resulted in the inadvertent structural incorporation of the given reaction solvent (dimethylsulfoxide or acetonitrile) in the final reaction step to 28 , affording by‐products 39 and 40 , respectively (Figure ) . Additionally, Košmrlj and co‐workers have recently reported the detection of methyl 2‐acetamido‐3,3‐dimethylbutanoate ( 41 ) in test purchase recreational samples of 5F‐MDMB‐P7AICA ( 25 ) . Amide impurity 41 has been proposed to form via amidation of ethyl acetate (a potential solvent used in the manufacture of 5F‐MDMB‐P7AICA [ 25 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Subsequently, Martek et al have provided an elegant protocol for the identification and differentiation between 4-, 5-, 6-, and 7-azaindole isomers of SCRA 27 using 1 H- 15 N HMBC NMR spectroscopy. 21 Considering the analytical challenges associated with the accurate identification and unambiguous structural elucidation of newly emerging NPS containing multiple nitrogen core atoms, we sought to highlight the chemical synthesis and describe the spectroscopic characterization and differentiation of a set of four novel isomeric 4-, 5-, 6-, and 7-azaindazole analogs (28)(29)(30)(31), employing the known potent indazole SCRA, MDMB-PINACA 32 as the exemplar (Figure 4). 22 Notably, MDMB-PINACA (32) shares close structural similarity with its 5-fluoro congener, 5F-MDMB-PINACA, an SCRA that has been implicated in several cases of fatal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…18 Similarly, following the test purchase of a sample marketed online as 4‐azaindole 26 (5F‐MDMB‐P4AICA) in 2017, further confirmation of structure using 1‐ and 2‐D nuclear magnetic resonance (NMR) experiments, including 1 H‐ 13 C heteronuclear multiple bond correlation (HMBC), revealed that it was in fact the 7‐azaindole isomer 27 20 . Subsequently, Martek et al have provided an elegant protocol for the identification and differentiation between 4‐, 5‐, 6‐, and 7‐azaindole isomers of SCRA 27 using 1 H‐ 15 N HMBC NMR spectroscopy 21 …”
Section: Introductionmentioning
confidence: 99%